Pengaruh Variasi Dosis Dekstrometorfan Terhadap Kadar Serum Glutamic Pyruvic Transaminase dan Gamma Glutamyl Transferase Pada Tikus Wistar - Iswari, Ni Wayan Gita; Putra, I Gusti Putu Agus Ferry Sutrisna; Widayanti, Ni Putu (Bali International University, 2020)
Background: Dextromethorphan is an antitussive drug commonly found in cough medicine, besides that dextromethorphan has the function as an expectorant or cough suppressant. Dextromethorphan is widely misused by the community, especially adolescents. Objective: to determine the effect of variations in dextromethorphan doses on SGPT and GGT levels in wistar rats. Method: using an experimental research design using the pretest-posttest control group design method. The analysis technique uses SPSS One Way Annova analysis. Results: Giving doses of dextromethorphan can increase levels of SGPT and GGT, namely in group P1 of 5.68% and 14.06%, P2 of 16.67% and 26.82%, and P3 of 20.95% and 36.54 %. Conclusion: There are effects of variations in dextromethorphan doses on increasing levels of SGPT and GGT in Wistar rats. Suggestion: It is necessary to conduct examination parameters and need to do research with more varied and longer doses.